ANALYSIS OF BANKING PROFITABILITY LEVEL (STUDY CASE OF PT.BANK TABUNGAN NEGARA (PERSERO) TBK PERIOD 2007-2015) - Maharanie Puspadewi Santoso (Jurnal Ilmiah Mahasiswa FEB, 2015)
Bank is a financial institution which is the executor of fiscal policies in a country. Besides, bank also helps supporting the people’s life by providing financial services. The success of a company, no exception bank, can be seen from its financial performance. Profitability level has been chosen by the previous researchers to illustrate the financial performance of a company. This research aims to analyze the factors that influence the profitability level of PT. Bank Tabungan Negara (PERSERO) Tbk or bank BTN. Dependent variable used in this research is profitability, which is illustrated by ROE ratio. The independent variables of this research are Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non Performing Loans (NPL), Net Interest Margin (NIM), Debt to Equity Ratio (DER), Operational Expense to Operational Income Ratio (BOPO), dan total credit. The research method used in this research is multiple regression analysis. The result of this research shows that CAR, DER, BOPO, and total credit significantly influence the profitability level of bank BTN, while LDR, NPL, and NIM are proved don’t. CAR and DER has a positive influence to profitability level, while BOPO and total credit has a negative influence to profitability level.Keywords:       Profitability, CAR, LDR, NPL, NIM, DER, BOPO, credit, multiple regression analysis, bank BTN.